Ged basics ebook - Peterson's (2012)
Peterson's GED Basics provides a quick and thorough way for students to prepare for the GED exam. This essential GED test-prep guide includes hundreds of practice questions, along with subject review and expert test-taking tips on how to score high on each GED test. Readers can quickly find pertinent information about the GED—where to take it, what's on the test, how the test is scored, when results are sent, and if one can take the GED more than once. Need extra subject help? In the Social Studies, Science, and Math chapters of GED Basics, readers will see easy-to-use links to HippoCampus.org, an innovative Web site where interactive subject help is offered via high-quality multimedia lessons and course content. HippoCampus™ is a project of the Monterey Institute for Technology and Education (MITE), supported by The William and Flora Hewlett Foundation, and designed as part of Open Education Resources (OER).